![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(S=1+3+5...+\left(2n-1\right)\)
Ta thấy \(1+\left(2n-1\right)=2n;3+\left(2n-3\right)=2n...;n+\left(2n-n\right)=2n\)
\(\Rightarrow S=\dfrac{n}{2}.2n=n^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
â) Ta có : \(2n-1⋮n+1\Leftrightarrow2n+2-2-1⋮n+1\)
\(\Leftrightarrow2\left(n+1\right)-2-1⋮n+1\)\(\Leftrightarrow2\left(n+1\right)-3⋮n+1\)
\(\Leftrightarrow2n-1⋮n+1\)khi \(3⋮n+1\Rightarrow n+1\in\)Ước của \(3\) \
\(\Leftrightarrow n+1\in\left(1;-1;3;-3\right)\)
\(\Leftrightarrow n\in\left(0;-2;2;-4\right)\)
Vậy \(n\in\left(-4;-2;0;2\right)\)
b) Ta có :\(9n+5⋮3n-2\Rightarrow3\left(3n-2\right)+6+5⋮3n-2\)
\(\Rightarrow3\left(3n-2\right)+11⋮3n-2\)
\(\Rightarrow9n+5⋮3n-2\)Khi \(11⋮3n-2\)
\(\Rightarrow3n-2\in U\left(11\right)\)
\(\Rightarrow3n-2\in\left(-11;-1;1;11\right)\)
\(\Rightarrow n\in\left(-3;1;\right)\)
Phần c) bạn tự làm nhé!
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{1}{1.6}+\frac{1}{6.11}+...+\frac{1}{n\left(n+5\right)}\)
\(A=\frac{1}{5}\left(\frac{5}{1.6}+\frac{5}{6.11}+...+\frac{5}{n\left(n+5\right)}\right)\)
\(A=\frac{1}{5}\left(\frac{6-1}{1.6}+\frac{11-6}{6.11}+...+\frac{n+5-n}{n\left(n+5\right)}\right)\)
\(A=\frac{1}{5}\left(1-\frac{1}{6}+\frac{1}{6}-\frac{1}{11}+...+\frac{1}{n}-\frac{1}{n+5}\right)\)
\(A=\frac{1}{5}\left(1-\frac{1}{n+5}\right)\)
\(A=\frac{n+4}{5n+25}\)
\(B=1.2+2.3+3.4+...+n\left(n+1\right)\)
\(3B=1.2.3+2.3.3+3.4.3+...+n\left(n+1\right).3\)
\(3B=1.2.3+2.3.\left(4-1\right)+3.4.\left(5-2\right)+...+n\left(n+1\right)\left[\left(n+2\right)-\left(n-1\right)\right]\)
\(3B=1.2.3-1.2.3+2.3.4-2.3.4+3.4.5-...-\left(n-1\right)n\left(n+1\right)+n\left(n+1\right)\left(n+2\right)\)
\(3B=n\left(n+1\right)\left(n+2\right)\)
\(B=\frac{n\left(n+1\right)\left(n+2\right)}{3}\)
Tổng: \(S=1+3+5+..+\left(2n-3\right)+\left(2n-1\right)\)
Ta có:
\(1+\left(2n-1\right)=1+2n-1=2n\)
\(3+\left(2n-3\right)=3+2n-3=2n\)
\(5+\left(2n-5\right)=5+2n-5=2n\)
.....
\(n+\left(2n-n\right)=n+2n-n=2n\)
Vậy tổng của dãy S là:
\(S=\dfrac{n}{2}\cdot2n=\dfrac{n\cdot2n}{2}=\dfrac{2n^2}{2}=n^2\)